Self‐Structural Healing of Encapsulated Perovskite Microcrystals for Improved Optical and Thermal Stability. Issue 21 (31st March 2021) - Li, Ruxue; Li, Bobo; Fang, Xuan; Wang, Dengkui; Shi, Yueqing; Liu, Xiu; Chen, Rui; Wei, Zhipeng
Abstract: Perovskite materials and their optoelectronic devices have attracted intensive attentions in recent years. However, it is difficult to further improve the performance of perovskite devices due to the poor stability and the intrinsic deep level trap states (DLTS), which are caused by surface dangling bonds and grain boundaries. Herein, the CH3 NH3 PbBr3 perovskite microcrystal is encapsulated by a dense Al2 O3 layer to form a microenvironment. Through optical measurement, it is found that the structure of perovskite can be healed by itself even under high temperature and long‐time laser illumination. The DLTS density decreases nearly an order of magnitude, which results in 4–14 times enhancement of light emission. The observation is ascribed to the micron‐level environment, which serves as a self‐sufficient high‐vacuum growth chamber, where the components of the perovskite are completely retained when sublimated and the decomposed atoms can re‐arrange after thermal treatment. The modified structure showing high thermal stability is able to maintain excellent optical and lasing stability up to 2 years. This discovery provides a new idea and perspective for improving the stability of perovskite and can be of practical interest for perovskite device application. Abstract : A self‐sufficient micrometer‐level vacuum growth chamber is proposed for MAPbBr3 microcrystals to effectively prevent water and oxygen, and to greatly improve the thermal and optical stability by the reduction of deep level trap states.